Retracted : Pengeluaran Pemerintah dan Indeks Pembangunan Manusia (IPM) Di Provinsi Bengkulu - Aan Zulyanto (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2018)
Human Development Index (HDI) is one indicator to evaluate the government performance. This index is consist of several main components such as education, health, and economy. This study aims to see how the effect of government spending on education, health, and infrastructure on the Human Development Index in the province of Bengkulu. It also analyzes the differences of HDI level in main and proliferation region as a response to regional autonomy in Indonesia. This Study uses panel data for kabupaten-kota in Bengkulu province during the period 2007-2013. It uses Random Effect Model (GLS) as estimation technique, based on formal testing against several estimation techniques associated with panel data. The results are the education spending has significant positive effect on the HDI. Substantial budget allocations for education that can improve HDI in Bengkulu province. While health and infrastructure spending are not significant, but it shows a negative relationship. It indicates the inefficiency and inaccuracy targets of the health budget and infrastructure in the Bengkulu province. Meanwhile, the study also finds a significant difference in the level of HDI, where main regions have HDI levels higher than the expansions.